Figures of speech : six histories of language & identity in the age of revolutions - Cassedy, Tim, 1981- (Impressions (Series) (University of Iowa Press), 2018)
"This study examines the role that language played at the turn of the nineteenth century as an immediate identifier of nationality. During this time of revolution (U.S., French, and Haitian), language served as a key identifier to quickly and conveniently categorize people within a globalizing world dominated by British and French empires. Linguistic differences, especially among English-speakers, seemed to validate the emerging national, racial, local, and regional identity categories that took shape in the wake of this new world order"--